Effect of single-dose intravenous dexamethasone on postoperative pain and postoperative nausea and vomiting in patients undergoing lower segment cesarean section under spinal anesthesia - Memon, Nazima; Bagga, Juhi (Asian Journal of Medical Sciences, 2022)
Background: Lower segment caesarean sections (LSCS) are commonly done under spinal anaesthesia. Although spinal anaesthetic techniques are relatively safe and associated with quick and uneventful recovery, post-operative pain is a major concern after effect of spinal anaesthesia weans off. Other than pain postoperative nausea and vomiting (PONV) is one of the important side effects of spinal anaesthesia. Steroids by virtue of their anti-inflammatory effect is expected to reduce pain consequent upon inflammation and many studies have shown their efficacy in reducing pain as well as PONV in post-operative patients. Aims and Objectives: Primary objective of the study was to evaluate efficacy of single-dose dexamethasone in reducing post-operative pain. The secondary objectives were to analyse effect of single-dose dexamethasone on hemodynamic stability as well as incidence of nausea and vomiting in patients undergoing LSCS under spinal anesthesia. Materials and Methods: This was a double-blind comparative study in which 60 patients undergoing LSCS under spinal anaesthesia were included on the basis of a predefined inclusion and exclusion criteria. Written informed consent was obtained from all patients. The patients were divided into two groups: Group D: 30 patients who received IV dexamethasone 8 mg (2 ml) intravenously just before giving spinal anesthesia. Group N: 30 patients who received Normal saline (2 ml) immediately before spinal anesthesia. In both groups, hemodynamic parameters, respiratory rate, severity of post-operative pain, and incidence of PONV was compared. P value less than 0.05 was taken as statistically significant. Results: Patients in Group D had significantly less severe post-operative pain (as assessed by the Visual analog scale) and incidence of PONV (P<0.05). Significantly less post-operative rescue analgesia was required in patients who received single dose of intravenous dexamethasone (P<0.05). In terms of hemodynamic stability, both groups were found to be comparable with no statistically significant difference. Conclusion: Single-dose dexamethasone is effective in reducing post-operative pain as well as incidence of PONV in patients undergoing LSCS under spinal anesthesia.